Very High Solid State Photoluminescence Quantum Yields of Poly(tetraphenylethylene) Derivatives. Issue 22 (26th September 2016) - Baysec, Sebnem; Preis, Eduard; Allard, Sybille; Scherf, Ullrich
Abstract : Five different poly(arylene‐diarylvinylene)s have been synthesized by reductive polyolefination starting from the corresponding bis(α, α‐dichlorobenzyl)‐substituted monomers and dicobaltoctacarbonyl as reducing agent. The resulting polymers all contain main chain tetraphenylethylene units. Thanks to the aggregation‐induced emission effect, the corresponding polymer films show remarkably high photoluminescence quantum yields (PLQYs) of 32%–73%. The polymer with the highest PLQY is tested as solid state sensing material for the PL‐quenching‐based detection of nitroaromatic analytes (1, 3, 5‐trinitrobenzene as prototypical analyte). Abstract : Poly(arylene‐diarylvinylene) homopolymers can be generated in dehalogenative polyolefination procedures. They show very high solid state photoluminescence quantum yields of up to 73% and have been used for the high sensitivity fluorometric detection of nitroaromatic compounds.